Analisis Akuntabilitas Pengelolaan Bantuan Pangan Nontunai pada Masa Pandemi Covid-19 (Studi Kasus pada Pemerintah Kabupaten Garut) - Refy Amalia Putri; Endah Dwi Kusumastuti; Ira Novianty (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Abstract: One of the government’s policies in restoring the national economy from the effects of the Covid-19 pandemic is the noncash food assistance program. This program is a social assistance in the form of food that aims to increase the effectiveness and accuracy of social assistance distribution targets, and encourage inclusive finance. This study was conducted with the aim of knowing and explaining the implementation of accountability in the management of the Non-Cash Food Assistance program during the Covid-19 pandemic in the Garut Regency Government. The type of research used is qualitative research with a case study approach. Data collection techniques were by observation, interviews, and documentation studies. Based on the results of the research, it shows that the accountability of the management of the program has been carried out well. However, there is still accountability that has not running well still needs to be improved, so that program implementation can be maximized. Keywords : Accountability, Noncash Food Assistance